2002
DOI: 10.1177/070674370204700610
|View full text |Cite
|
Sign up to set email alerts
|

Senior Residents in Psychiatry: Views on Training in Developmental Disabilities

Abstract: Senior residents also desire curricular enhancements that experts in developmental disabilities have long recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…This result differs from the findings of one of the Canadian surveys, in which 59 percent of the residents who underwent specialized training in the field of mental retardation recommended additional training (8). This result differs from the findings of one of the Canadian surveys, in which 59 percent of the residents who underwent specialized training in the field of mental retardation recommended additional training (8).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This result differs from the findings of one of the Canadian surveys, in which 59 percent of the residents who underwent specialized training in the field of mental retardation recommended additional training (8). This result differs from the findings of one of the Canadian surveys, in which 59 percent of the residents who underwent specialized training in the field of mental retardation recommended additional training (8).…”
Section: Discussioncontrasting
confidence: 82%
“…A recent study found that less than half of the Canadian psychiatric training programs provided mandatory clinical experience in the field of mental retardation (7). Another Canadian study reported that 59 percent of senior psychiatry residents thought that more training on developmental disabilities was needed in their residency programs (8). Although Canadian and Australian educators have begun to examine this issue (4,(7)(8)(9), there is a lack of data that examines U.S. psychiatry residents' perceptions of developmental disabilities training.…”
Section: -314 2004)mentioning
confidence: 99%
“…Given the limited amount of research on this topic, studies that used measures of attitudes to people with disabilities (i.e., studies that did not use IDspecific measures) to assess participants' attitudes to people with ID were included, as were studies whose participants were a combination of medical students and professionals or other students. The authors agreed to exclude the following types of articles: examinations of medical students' views on training in ID, which did not assess participants' attitudes towards people with ID and/or their healthcare (e.g., Burge, Ouellette-Kuntz, Isaacs, & Lunsky, 2008;Burge, Ouellette-Kuntz, McCreary, Bradley, & Leichner, 2002); studies without a focus on ID (e.g., Beausoleil, Zalneraitis, Gregorio, & Healey, 1994;Wonkam, Njamnshi, & Angwafo, 2006); and research without medical students (e.g., Boyle et al, 2010;Parchomiuk, 2013). Then, the first author reviewed the literature.…”
Section: Review Processmentioning
confidence: 99%
“…Surveys of psychiatry residents regarding their education and training in specific disorders and issues have provided useful information for enhancing psychiatric residency program curricula (e.g., Barnard-Thompson & Leichner, 1999;Burge, Ouellette-Kuntz, McCreary, Bradley & Leichner, 2002). With respect to eating disorders (EDs), the American Psychiatric Association ([APA], 2000) has stated that treatment requires expertise, including psychiatric evaluation and monitoring.…”
Section: A Time Cohort Comparison Was Conducted Via Questionnaire Wmentioning
confidence: 99%